To determine which of the given equations has the same solutions as \((x-7)(x+9)=0\), we first solve \((x-7)(x+9)=0\).
Setting each factor to zero gives us:
- \(x - 7 = 0 \Rightarrow x = 7\)
- \(x + 9 = 0 \Rightarrow x = -9\)
So, the solutions are \(x = 7\) and \(x = -9\).
Now, let's evaluate each of the given options to see which one has exactly the same solutions.
-
\(x^2 + 2x = -63\)
Rearranging gives: \[ x^2 + 2x + 63 = 0 \] The discriminant is \(2^2 - 4 \cdot 1 \cdot 63 = 4 - 252 = -248\), which means there are no real solutions.
-
\(x^2 - 2x - 63 = 0\)
We can factor this as: \[ (x-9)(x+7) = 0 \] Setting each factor to zero gives us solutions \(x = 9\) and \(x = -7\), which are different from \(7\) and \(-9\).
-
\(x^2 = 2x - 63\)
Rearranging gives: \[ x^2 - 2x + 63 = 0 \] The discriminant is \((-2)^2 - 4 \cdot 1 \cdot 63 = 4 - 252 = -248\), which means there are no real solutions.
-
\(x^2 = -2x + 63\)
Rearranging gives: \[ x^2 + 2x - 63 = 0 \] We can factor this as: \[ (x + 9)(x - 7) = 0 \] Setting each factor to zero gives us solutions \(x = -9\) and \(x = 7\), which matches our original solutions.
Thus, the equation that has exactly the same solutions as \((x-7)(x+9)=0\) is:
\(x^2 = -2x + 63\).